Characteristics and Biomarkers of Ferroptosis - Chen, Xin; Comish, Paul B.; Tang, Daolin; Kang, Rui (Frontiers in Cell and Developmental Biology, 2021)
The induction and consequences of regulated cell death (RCD) are accompanied by changes in gene and protein expression, biochemical pathways, as well as cell morphology and size. Such RCDs have a significant impact on development, tissue homeostasis, and the occurrence and progression of disease. Among different forms of RCD, ferroptosis appears to be the main cause of tissue damage driven by iron overload and lipid peroxidation. In fact, the dysfunctional ferroptotic response is implicated in a variety of pathological conditions and diseases, such as neurodegenerative diseases, tissue ischemia-reperfusion injury, tumorigenesis, infections, and immune diseases. Ferroptotic response can be fine-tuned through various oxidative stress and antioxidant defense pathways, coupling with metabolism, gene transcription, and protein degradation machinery. Accordingly, a series of important ferroptosis inducers or inhibitors targeting redox- or iron metabolism-related proteins or signal transduction have been developed. Although this kind of RCD has recently attracted great interest in basic and clinical research, detecting and monitoring a ferroptotic response still faces challenges. In this mini-review, we not only summarize the latest knowledge about the characteristics of ferroptosis in vitro and in vivo, but also discuss the specificity and limitations of current biomarkers of ferroptosis.